2018
DOI: 10.1101/255794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binding during sequence learning does not alter cortical representations of individual actions

Abstract: 37As a movement sequence is learned, serially ordered actions get bound together into sets in order 38 to reduce computational complexity during planning and execution. Here we examined how the 39 binding of serial actions alters the cortical representations of individual movements. Across five 40 weeks of practice, healthy human subjects learned either a complex 32-item sequence of finger 41 movements (Trained group, N=9) or randomly ordered actions (Control group, N=9). After five 42 weeks of training, respo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Importantly, no significant changes in representational magnitude were found in the contralateral primary somatosensory cortex after consolidation. This is in line with the fact that M1 representational geometry has been shown to be strongly shaped by ecological finger co-activations (Ejaz et al, 2015), and to be resistant to extensive training of a sequence built on a new co-activation structure (Beukema et al, 2018). This negative result complements that of Figure 2, supporting that primary representation uncovered there might not reflect sequential features but the interaction of pre-existing somatotopic organization and single finger position in each sequences.…”
Section: Discussionsupporting
confidence: 78%
“…Importantly, no significant changes in representational magnitude were found in the contralateral primary somatosensory cortex after consolidation. This is in line with the fact that M1 representational geometry has been shown to be strongly shaped by ecological finger co-activations (Ejaz et al, 2015), and to be resistant to extensive training of a sequence built on a new co-activation structure (Beukema et al, 2018). This negative result complements that of Figure 2, supporting that primary representation uncovered there might not reflect sequential features but the interaction of pre-existing somatotopic organization and single finger position in each sequences.…”
Section: Discussionsupporting
confidence: 78%
“…This may explain why the anophthalmic individuals’ S1 hand representation is not different from that of sighted controls. As a measure strongly correlated to everyday hand use (Ejaz et al 2015), the canonical structure of hand representation has been found to be remarkably stable, despite hand loss (Kikkert et al 2016, Wesselink et al 2019), extensive behavioural training (Beukema et al 2019), or expert musicianship (Ogawa et al 2019). While average dissimilarity between fingers may vary, indicating altered signal strength, the representational structure is stable.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step, separately for each run, we suppressed correlated noise across voxels by applying the multivariate noise normalization. We then computed the dissimilarity (d i,j ) between the activation patterns (u) of a pair of stimuli (i,j) using a leave-one-out cross validation scheme as follows (Beukema et al 2019 ): where M represents the independent partitions (cross-validation folds), and T the number of time points. Distances were computed in each pair of runs ( l , m ) and then averaged across each possible combination of runs.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-validation also allows negative crossnobis distances, if the pattern of activity of each stimulus is not consistent and, consequently, a given area is not reliably able to encode differences between them. The meaningful zero point allows testing cross-validated Mahalanobis distances against zero to assess whether an area significantly discriminates between a pair of stimuli (i.e., the average distance will be significantly higher than zero) or not (Beukema et al 2019 ; Diedrichsen et al 2016 ; Diedrichsen and Kriegeskorte 2017 ; Walther et al 2016 ). Furthermore, it is also possible to compare distances between two or more pair of stimuli by means of two-sample or paired t -tests, to assess whether a distance is higher than others (Diedrichsen et al 2016 ; Walther et al 2016 ; Yokoi et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation